Determinants of Antibiotic Prescribing for Upper Respiratory Tract Infections in Sana’a City, Yemen - Abdulrazzaq Y. Al-Khazzan; Doa’a A. Ibrahim; Abdulsalam M. Halboup; Sabariah N. Harun; Shatha Al Dhubai; Noor Hayal; Hajer Alhazwarah; Aisha Shaaban; Afraa Alsabri; Soha Al-Thalje; Abdullah A. Areqi; Ammar A. S. Jaber (University of Science and Technology, Sana’a, Yemen, 2024)
Background: Antibiotics are frequently overprescribed for upper respiratory tract infections (URTIs) in outpatient settings, especially in regions with fragile health systems. Therefore, the present study assessed the patterns and predictors of antibiotic prescribing for URTIs in Sana’a city, Yemen. Methods: A cross-sectional study was conducted among 453 conveniently sampled patients with URTIs in the pediatric and ear, nose and throat (ENT) clinics in six public and private referral hospitals in Sana’a from July to September 2019. Demographic characteristics of patients and physicians, as well as data on the likely types of URTIs and prescribed antibiotics, were collected using a validated questionnaire. The data were then analyzed using univariate and multivariable binary logistic regression, with a significance level of less than 0.05. Results: Of 453 patients with URTIs, 429 (94.7%) received antibiotics in the pediatric and ENT outpatient clinics of the study hospitals. More than half of antibiotic prescriptions were prescribed by physicians who were male (54.7%), experienced for 15 years or fewer (53.2%), and pediatricians (51.2%). On the other hand, most prescriptions (73.7%) were prescribed by physicians aged ≤45 years. Penicillins were the most frequently prescribed antibiotics (44.3%), followed by macrolides (25.9%), and cephalosporins (17.2%). However, antifolates (0.9%) and fluoroquinolones (11.7%) were the least frequently prescribed. Amoxicillin-clavulanate (38.9%) was the most frequently prescribed antibiotic for URTIs, followed by azithromycin (16.1%), clarithromycin (9.8%), and cefdinir (5.7%). In multivariable analysis, female physicians were more likely to prescribe antibiotics than males (AOR = 4.5, 95% CI: 1.49–13.33; P = 0.007), while ENT specialists were less likely compared to pediatricians (AOR = 0.2, 95% CI: 0.07–0.84; P = 0.025). Conclusion: The rate of prescribing antibiotics for URTIs among outpatients in Sana’a is high, with a high proportion of inappropriate prescriptions for infections that are unlikely to be bacterial. Penicillins, particularly amoxicillin-clavulanate, are most often prescribed. Various factors related to patients and physicians can influence physicians’ prescribing behavior, emphasizing the need for targeted interventions to rationalize antibiotic prescribing for treating URTIs. Further research is needed to address antibiotic prescribing patterns in the clinical context.